Pengaruh Modal Usaha, Tenaga Kerja, dan Penggunaan E-commerce Terhadap Pendapatan UMKM Bidang Kuliner di Kota Denpasar - Putu Yasti Putri Arniyasa; Ni Luh Karmini (Universitas 17 Agustus 1945 Semarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive business units that stand alone, which are carried out by individuals or business entities in all economic sectors. The existence of Micro, Small and Medium Enterprises (MSMEs), which is the largest part of the national economy, is an indicator of the level of community participation in various sectors of economic activity. The purpose of this study was to determine and analyze the simultaneous and partial effects of business capital, labor, and use of e-commerce variables on Culinary MSME income in Denpasar City. This study used the accidental proportional sampling method with a sample of 99 MSME actors in the culinary field in Denpasar City. The data analysis technique used is multiple linear regression analysis. The results of data processing and simultaneous testing show that capital, labor, and the use of e-commerce have a significant effect on the income of MSMEs in the culinary field in Denpasar City. The results of data processing also show that the variables of business capital and labor partially have a positive and significant effect on the income of culinary MSMEs in Denpasar City. MSMEs in the culinary field in Denpasar City who use e-commerce earn higher incomes compared to those who do not use e-commerce.